Implementation of Database Architecture and Interface Design for the Interactive Urban Navigation System of Icherisheher - Algayeva, Huru (ADA University, 2025)
The study examines the development of an interactive urban navigation system to be relevant to historical urban areas, such as by the case study of Icherisheher, UNESCO World Heritage site in Baku, Azerbaijan. Indeed, the emphasis in this case, also, would be addressing major inefficiencies in the conventional navigation systems by not accommodating complex layout and cultural significance of historical areas. Here, the transformation from a traditional navigation system into an active exploration activity is achieved using innovative geocaching features, sophisticated database architecture, and an interface design user-centric. The two basic technological innovations are comprehensive feature modelling system and an image validation system that uses computer vision to verify whether or not specific caches have been discovered once accuracy exceeds a pre-defined threshold. This way, gamification seeks to promote exploration fun but still encourage a larger cultural heritage engagement. The design implementation is a configuration of database frameworks via Docker containerization technology, thus enabling the integration of a PostgreSQL database with PostGIS extensions for spatial data management and a Neo4J graph database for representing relationships into a viable dual database model that works well for handling complex geospatial queries and relational data. The user interface places intuitive navigation as a primary objective, in addition to specifying multiple routes-as new, old, cultural, tourist-optimized, generous and scenic, real-time location tracking, and an engaging gamification system. Increases more user involvement in the geocaching interface dynamically,through inclusion of location triggers, image upload mechanisms, and progress tracking during geocaching game. This research establishes the contours of urban informatics and human-computer interaction by demonstrating the idea that gamification elements indeed enhance the experience of cultural tourism. Deployment through Docker significantly increases the reliability and scalability of the system and enacts a data integrity policy through comprehensive validation and performance testing protocols. This framework thus offers a paradigm for similar implementations in historical urban areas across the globe in marrying technology innovation with cultural preservation for more interactive and informative navigation experiences.
Keywords: Geocaching -- Design and construction.; Human-computer interaction -- Research.; Urban navigation systems -- Technological innovations.; Cultural heritage -- Conservation and restoration -- Technological innovations.; IT and Engineering